The noun phrase as an emergent unit in Finnish - Helasvuo Marja-Liisa (John Benjamins Publishing Company, 2022)
The article focuses on the use of noun phrases in Finnish conversation as arguments, contrasting these uses with the use of free NPs. I show that several grammatical processes characteristic of Finnish contribute to making the internal structure of NPs relatively stable. Agreement in case and number, together with the relatively fixed ordering of elements within the NP, help the co-participants to project the future course of the turn. In the construction of NPs as referring expressions, recipient design is an important preference. A close examination of the use of argument NPs and free NPs in interaction reveals different clusterings of features characteristic of NPs as units. Based on these findings, the NP emerges as a robust unit in Finnish.
The 'Noun Phase' across Languages. An emergent unit in interaction